Stillbirth, hypertensive disorders of pregnancy, and placental pathology. (July 2016) - Gibbins, Karen J.; Silver, Robert M.; Pinar, Halit; Reddy, Uma M.; Parker, Corette B.; Thorsten, Vanessa; Willinger, Marian; Dudley, Donald J.; Bukowski, Radek; Saade, George R.; Koch, Matthew A.; Conway, Deborah; et al.
Abstract: Introduction: Stillbirth, preeclampsia, and gestational hypertension (PE/GH) have similar clinical risk factors and redundant placental pathology. We aim to discern if stillbirth with PE/GH has a particular phenotype by comparing stillbirths with and without PE/GH. Methods: Secondary analysis of the Stillbirth Collaborative Research Network, a population-based cohort study of all stillbirths and a sample of live births from 2006 to 2008 in five catchment areas. We compared placental pathology between stillbirths and with and without PE/GH, stratified by term or preterm. We also compared placental pathology between stillbirths and live births with PE/GH. Results: 79/518 stillbirths and 140/1200 live births had PE/GH. Amongst preterm stillbirths, there was higher feto-placental ratio in PE/GH pregnancies (OR 1.24 [1.11, 1.37] per unit increase), and there were more parenchymal infarctions (OR 5.77 [3.18, 10.47]). Among PE/GH pregnancies, stillbirths had increased maternal and fetal vascular lesions, including retroplacental hematoma, parenchymal infarction, fibrin deposition, fetal vascular thrombi, and avascular villi. Discussion: Stillbirth pregnancies are overwhelmingly associated with placental lesions. Parenchymal infarctions are more common in PE/GH preterm stillbirths, but there is significant overlap in lesions found in stillbirths and PE/GH. Highlights: Parenchymal infarcts are increased in "more severe" disease, whether that is PE/GH in preterm stillbirths or stillbirth in PE/GH pregnancies. Low feto-placental weight ratios are associated with stillbirth. In term stillbirths, there are no notable differences between pregnancies affected and unaffected by PE/GH.